Frequency of Ventilator-Associated Pneumonia in PICU at NICH - Shahid, Afifa; Ali Gova, Murtaza; Noor, Noshaba; Chandio, Bakhtawar; Jamal, Ghazala; Nawaz, Hira (Biological and Clinical Sciences Research Journal, 2025)
Ventilator-associated pneumonia (VAP) is one of the most common and severe nosocomial infections in intensive care settings, especially in pediatric populations. Objective: To determine the frequency of VAP among mechanically ventilated children in the PICU of NICH, identify the causative pathogens, and assess their antimicrobial susceptibility patterns. Methods: This cross-sectional study was conducted at the PICU of NICH, Karachi, from May 2024 to November 2024, and enrolled pediatric patients aged 1 month to 15 years who required intensive care and mechanical ventilation. A total of 86 ventilated pediatric patients were enrolled. Patients who met the inclusion criteria were enrolled following informed consent. Clinical and demographic data were recorded on a structured, IERB-approved proforma, including patient age, gender, diagnosis, date and time of intubation, medications, and surgical interventions. Results: Out of 86 patients, 62 (72.09%) developed VAP. The mean duration of mechanical ventilation was 14.95 ± 4.5 days, and the mean hospital stay was 18.53 ± 6.0 days. The mortality rate among VAP patients was 56.45%. Acinetobacter spp. (59.68%) and Pseudomonas spp. (38.71%) were the most commonly isolated pathogens. Resistance rates were extremely high, with Acinetobacter spp. Showing 100% resistance to meropenem, ceftriaxone, amikacin, and other first-line antibiotics. Only 5.41% of isolates were sensitive to ciprofloxacin. The mean CPIS score was 6.68 ± 1.62. Conclusion: It is concluded that VAP is highly prevalent in the PICU at NICH and is associated with high mortality and prolonged hospital stay. The predominance of multidrug-resistant organisms, especially Acinetobacter spp., underscores the urgent need to implement stringent infection control practices, routine surveillance, and stewardship-driven antibiotic protocols to manage and reduce the burden of VAP.